ANALYSIS OF PARAMETERS INFLUENCING PERIOD OF VEGETABLE SEMI-FINISHED PRODUCTS FREEZING WITH COMBINED METHOD - Korotkiy I.A.; Sahabutdinova G.F.; Shafrai A.V. (Техника и технология пищевых производств, 2017)
The combined method of freezing combines the product convectional freezing and subsequent contact storage on a cooled metal plate. This method is used to freeze vegetable semi-finished products that have been pre-packed in a vacuum package. Advantages of the combined method are the absence of product shrinkage, loss of aromatic properties, and reduction of temperature fluctuations during the process, sparing operating conditions in the packing area. Freezing period is an important characteristic of the process. The prediction of the freezing period is the most difficult task in thermophysics, since there are many parameters affecting the freezing process. The article presents the results of the research revealing the degree of temperature influence inside the freezing chamber, the rate of air movement and the layer thickness of the product to be frozen in the package. It has been proved that the freezing period of the vegetable mix is more influenced by the temperature in the chamber t, the thickness of the frozen product δ and the joint influence of t-δ. Using the Statistica program for processing the experimental data on the freezing period a mathematical regression model has been obtained, which can predict the freezing period with high accuracy. The relative error between the experimentally obtained data and the predicted ones is less than 5%.